VCP inhibition induces an unfolded protein response and apoptosis in human acute myeloid leukemia cells - Szczęśniak, Paweł P.; Heidelberger, Jan B.; Serve, Hubert; Beli, Petra; Wagner, Sebastian A. (PLOS ONE, 2022)
Acute myeloid leukemia (AML) is a heterogeneous malignancy characterized by the accumulation of undifferentiated white blood cells (blasts) in the bone marrow. Valosin-containing protein (VCP) is an abundant molecular chaperone that extracts ubiquitylated substrates from protein complexes and cellular compartments prior to their degradation by the proteasome. We found that treatment of AML cell lines with the VCP inhibitor CB-5083 leads to an accumulation of ubiquitylated proteins, activation of unfolded protein response (UPR) and apoptosis. Using quantitative mass spectrometry-based proteomics we assessed the effects of VCP inhibition on the cellular ubiquitin-modified proteome. We could further show that CB-5083 decreases the survival of the AML cell lines THP-1 and MV4-11 in a concentration-dependent manner, and acts synergistically with the antimetabolite cytarabine and the BH3-mimetic venetoclax. Finally, we showed that prolonged treatment of AML cells with CB-5083 leads to development of resistance mediated by mutations in VCP. Taken together, inhibition of VCP leads to a lethal unfolded protein response in AML cells and might be a relevant therapeutic strategy for treatment of AML, particularly when combined with other drugs. The toxicity and development of resistance possibly limit the utility of VCP inhibitors and have to be further explored in animal models and clinical trials.